The Longitudinal Relationship Between Screen Time, Sleep and a Diagnosis of Attention-Deficit/Hyperactivity Disorder in Childhood. Issue 14 (December 2021) - Levelink, Birgit; van der Vlegel, Marjolein; Mommers, Monique; Gubbels, Jessica; Dompeling, Edward; Feron, Frans J.M.; van Zeben-van der Aa, Dorothea M.C.B.; Hurks, Petra; Thijs, Carel
Objective: To evaluate longitudinal associations between recreational screen time and sleep in early childhood, and attention-deficit/hyperactivity disorder (ADHD) at age 8 to 10 years. Method: Questionnaires from 2, 768 mother-child pairs from the Dutch KOALA Birth Cohort Study were used. General estimating equation logistic regression analyses examined associations between screen time and sleep at age 2, 4, and 6, and ADHD at age 8 to 10. Linear regression analysis examined associations between television time, sleep and CBCL/2-3 scores at age 2. Results: Longitudinally, neither screen time nor sleep were associated with ADHD. Cross-sectionally, CBCL/2-3 externalizing symptom scores increased by 0.03 with every hour television time (95% CI 0.002–0.05) and increased by 0.02 per hour of less sleep (95% CI −0.03–−0.01). Conclusion: Despite an association with externalizing symptoms at age 2, screen time and sleep in early childhood were not associated with ADHD. Carefulness is warranted when extrapolating cross-sectional associations at early age to an ADHD diagnosis.